Analisis Pengaruh Belanja Daerah Terhadap Pertumbuhan Ekonomi, Kemiskinan, dan Pengangguran di Kabupaten Muaro Jambi - Zuhriah, Zuhriah (e-Journal Perdagangan Industri dan Moneter, 2015)
The purpose of this research to identify and analyze the development of government expenditure, economic growth, poorness, and unemployment. And to identify and analyze the effect of government expenditure on economic growth, on poorness, and on unemployment in the Muaro Jambi Regency the period 2002-2013. Based of this research are the development average of government expenditure in the amount 18,1%, the development average of PDRB in the amount 17,75%, the development average of poorness in the amount -1,36%, and the development average of unemployment in the amount 43,60%. The analysis used is a simple regression method. The result is government expenditure has a positive value and a significant effect on economic growth (PDRB), government expenditure has a negative value and significant effect on poorness, and government expenditure has a positive value and has no effect on unemployment.